Evaluation of P‐glycoprotein (Pgp) expression in human osteosarcoma by high‐throughput tissue microarray. Issue 9 (2nd February 2016) - Gao, Yan; Liao, Yunfei; Shen, Jacson K.; Feng, Yong; Choy, Edwin; Cote, Gregory; Harmon, David; Mankin, Henry J.; Hornicek, Francis J.; Duan, Zhenfeng
ABSTRACT: Survival of osteosarcoma patients is currently limited by the development of metastases and multidrug resistance (MDR). A well‐established cause of MDR involves overexpression of P‐glycoprotein (Pgp) in tumor cells. However, some discrepancies still exist as to the clinical significance of Pgp in osteosarcoma. We sought to elucidate further whether the Pgp expression correlated with clinical behavior in a series of patients with osteosarcoma via high‐throughput tissue microarray (TMA) analysis. Immunohistochemical analysis of Pgp expression in a TMA of 114 specimens with a retrospective review of 70 osteosarcoma patients admitted to the Massachusetts General Hospital (MGH) was performed. High Pgp expression was correlated with metastasis development and poor response to pre‐operative chemotherapy in osteosarcoma patients. Eighteen of the fifty‐seven patients initially admitted with primary osteosarcoma showed high Pgp expression. Among these 18 patients with high Pgp expression, 13 of 18 (72%) patients eventually developed metastases. There was no significant clinical relevance between Pgp expression and osteosarcoma survival. These results support that high expression of Pgp is important, but cannot be assigned as, an individual predictor in the development of human osteosarcoma. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1606–1612, 2016.